ANALISIS PELAKSANAAN TUGAS DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN DI KOTA TANGERANG SELATAN DALAM MENANGANI KEBAKARAN DI KOTA TANGERANG SELATAN - Kurniawan, Eka; Mulyono, Doddy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This exploration aims to determine and dissect the perpetration of the duties of the South Tangerang Fire and Rescue Service in handling fires in South Tangerang City and the recommendations or suggestions that can be given. This exploration uses a qualitative descriptive system with data collection, observation, interviews and attestation styles. The results of the exploration show that in the analysis of the perpetration of the duties of the South Tangerang City Fire and Rescue Service in handling fires grounded on South Tangerang City Regional Regulation Number 4 of 2015 concerning operation of Fire Prevention and Management, videlicet through the process of original Departure Stage, Advanced Departure Stage, functional Extinguishing Stage, Deliverance and Extinguishing Phase Completed. It's just that it hasn't been done optimally and effectively, it still needs to be equipped with installations and structure for handling fires as well as education and chops training for fire fighters on a regular and nonstop base, and the obstacles include, among others, installations and structure are an important factor in furnishing services and mitigation. fire disaster. The lack of installations and structure will affect in detainments in the process of fire disaster operation services. The installations possessed by the South Tangerang City Fire and Rescue Service are considered to be still deficient, similar as the lack of fire lines, the lack of budgets and the lack of fire stations